Experimental Methods Applied in a Study of Stall Flutter in an Axial Flow Fan - John D. Gill; Vincent R. Capece; Ronald B. Fost (Shock and Vibration)
Flutter testing is an integral part of aircraft gas turbine engine development. In typical flutter testing blade mounted sensors in the form of strain gages and casing mounted sensors in the form of light probes (NSMS) are used. Casing mounted sensors have the advantage of being non-intrusive and can detect the vibratory response of each rotating blade. Other types of casing mounted sensors can also be used to detect flutter of rotating blades. In this investigation casing mounted high frequency response pressure transducers are used to characterize the part-speed stall flutter response of a single stage unshrouded axial-flow fan. These dynamic pressure transducers are evenly spaced around the circumference at a constant axial location upstream of the fan blade leading edge plane. The pre-recorded experimental data at 70% corrected speed is analyzed for the case where the fan is back-pressured into the stall flutter zone. The experimental data is analyzed using two probe and multi-probe techniques. The analysis techniques for each method are presented. Results from these two analysis methods indicate that flutter occurred at a frequency of 411 Hz with a dominant nodal diameter of 2. The multi-probe analysis technique is a valuable method that can be used to investigate the initiation of flutter in turbomachines.